2018
DOI: 10.1177/1360780418811973
|View full text |Cite
|
Sign up to set email alerts
|

(Re)imagining the ‘Backstreet’: Anti-abortion Campaigning against Decriminalisation in the UK

Abstract: is a senior lecturer in sociology and social policy. Her main research area is centred around women's reproductive and sexual health and she has research includes issues around birth control, pregnancy and motherhood. She has recently completed projects on the deployment of neuroscience in parenting and child sexual exploitation. Her most recent book Reproductive Health and Maternal Sacrifice: Women, Choice and Responsibility was published by Palgrave in 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It can here be useful to open a brief parenthesis on how the concept of ‘risk’ is constructed and manifested, as we as we cannot ignore the different moral basis used to identify what a risk is in public health interventions and their supporters (i.e., through the identification of identifiable harms and victims) and by the users behind the tweets analyzed (for which, the real risk is the alleged thread to their individual freedoms) (in line with Hunt 1999 ; Lowe 2019 ). For these latter, by reconceptualizing risk as danger rather than a balance of possibilities (see Fox 1999 ; Lee 2014 ), the COVID-19-related health risk would be nothing else than a way to justify surveillance and restrictions toward the population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can here be useful to open a brief parenthesis on how the concept of ‘risk’ is constructed and manifested, as we as we cannot ignore the different moral basis used to identify what a risk is in public health interventions and their supporters (i.e., through the identification of identifiable harms and victims) and by the users behind the tweets analyzed (for which, the real risk is the alleged thread to their individual freedoms) (in line with Hunt 1999 ; Lowe 2019 ). For these latter, by reconceptualizing risk as danger rather than a balance of possibilities (see Fox 1999 ; Lee 2014 ), the COVID-19-related health risk would be nothing else than a way to justify surveillance and restrictions toward the population.…”
Section: Resultsmentioning
confidence: 99%
“…For these latter, by reconceptualizing risk as danger rather than a balance of possibilities (see Fox 1999 ; Lee 2014 ), the COVID-19-related health risk would be nothing else than a way to justify surveillance and restrictions toward the population. As such, while the concept of risk has been utilized in this study as prevalent in the relevant literature, we should recognize that—as observed in Lowe ( 2019 )—the adoption of risk-based narratives can contain unresolved contradictions (shifting also the implicit burden of the related responsibility to manage that risk, e.g., from the uncompliant individual to the dystopic State) and consequently can be problematic in the context of public communication.…”
Section: Resultsmentioning
confidence: 99%
“…The supporters of abortion are looking for arguments for its legalization, also for cross-border purposes, e.g. indicating the risk of death or serious injury of illegal abortions, but without discussing the long-term and wide-ranging consequences for the quality of mental life or relations with the spouses of women who perform abortions (Lowe, 2018). In these two trends, there is talk of pro-life attitudes that indicates that human life should be protected from conception to natural death, and pro-choice attitudes, recognizing the right of women to choose abortion, due to the belief that it is her business.…”
Section: Attitudes Towards Abortionmentioning
confidence: 99%
“…We can point to precise acts of direct violence. For example, pro-life groups organize in front of abortion clinics to dissuade women with lies and encourage women and professionals to repent (Morgan, 2017;Lowe, 2019;Lowe and Page, 2019). The literature also shows that there is direct violence on the part of some health professionals.…”
Section: Direct Violence Against Abortionmentioning
confidence: 99%